Preoperative continuous positive airway pressure use improves the hospital experience of children undergoing adenotonsillectomy for obstructive sleep apnea - Zaballa, Katrina; Jayasuriya, Geshani; Waters, Karen (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Objective of the study was to determine how the preoperative use of continuous positive airway pressure (CPAP) in children diagnosed with obstructive sleep apnea (OSA), and their compliance with the therapy, impact perioperative outcomes of adenotonsillectomy. Methods: A retrospective chart review was conducted on patients diagnosed with OSA on polysomnography, who underwent adenotonsillectomy between 2011-2017. Comparisons were made between patients who were not prescribed CPAP (N-CPAP), prescribed CPAP but non-compliant (NC-CPAP), and those compliant with their CPAP prescription (C-CPAP) therapy. OSA severity was categorized by total apnea-hypopnea index into mild <5, moderate 5-10, and severe >10. Results: A total of 55 of the 162 patients (34%) were recommended CPAP. For those recommended CPAP, 25 were NC-CPAP and 30 C-CPAP. Compared to N-CPAP, NC-CPAP had a 47% reduction in wait time to surgery (p=0.0008) but 59% increase in LOS (p=0.001), while C-CPAP had 24% reduction in wait time (p=0.12) but 34% increase in LOS (p=0.026). Risk for post-operative admission to pediatric intensive care unit (PICU) was highest in NC-CPAP (OR=12 CI 3-44) and increased in C-CPAP (OR=9 CI 2-33). Children with severe OSA had higher frequency of postoperative CPAP use, NC-CPAP 29% and C-CPAP 64% (p≤0.0001). However, use of CPAP did not prevent a requirement for post-operative oxygen. Conclusions: Amongst children prescribed pre-operative CPAP, compliance with therapy had a positive impact on the patient hospital experience following adenotonsillectomy.